2010
DOI: 10.1080/10401334.2010.488201
|View full text |Cite
|
Sign up to set email alerts
|

Community Service and the Pediatric Exam: An Introduction to Clinical Medicine via a Partnership Between First Year Medical Students and a Community Elementary School

Abstract: The program provides a model for early clinical experience that embraces service learning. It instills an ethic of service and illustrates how the community can be a valuable teaching resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…They completed an advocacy course, internship, and scholarly activity. Questionnaire • Increased leadership skills • Increased teaching skills • Developed an understanding of health disparities that could be addressed by health education interventions, community partnerships, and changes to policy/legislative mandates McConnell et al, 2010 19 Required 1 year (data over 3 years) M1 (N = 301) Pediatric knowledge Lectures on health topics, provide physical exams to students from inner-city schools Pediatric exams, questionnaire • Learned to identify and address the health-needs of an underserved community • Increased teaching and presentation skills McNeal et al, 2012 20 Selective 2 to 3 months M1, M2, M3, and M4 Health behavior education Mini-grants awarded to student groups, groups conducted needs-assessments, held health a fare, and developed summer projects to address community needs Poster presentations, questionnaire • Developed leadership skills • Increased understanding of the social determinants of health • Developed understanding of health disparities that could be addressed by health education interventions, community partnerships, and changes to policy/legislative mandates Meili et al, 2011 21 Selective 2 years M1 and M2 (N = 14) Develop social accountability Service-learning program rotates through urban, rural, and international locations (students learn foreign language), qualitative data analysis conducted on open-ended questionnaires Reflective essay • Increased importance of patient-physician relationships • Developed multicultural understanding of community • Increased understanding of the social determinants of health • Increased sense of social justice • Recognized need to affect unhealthy habits of communities • Mixed...…”
Section: Resultsmentioning
confidence: 99%
“…They completed an advocacy course, internship, and scholarly activity. Questionnaire • Increased leadership skills • Increased teaching skills • Developed an understanding of health disparities that could be addressed by health education interventions, community partnerships, and changes to policy/legislative mandates McConnell et al, 2010 19 Required 1 year (data over 3 years) M1 (N = 301) Pediatric knowledge Lectures on health topics, provide physical exams to students from inner-city schools Pediatric exams, questionnaire • Learned to identify and address the health-needs of an underserved community • Increased teaching and presentation skills McNeal et al, 2012 20 Selective 2 to 3 months M1, M2, M3, and M4 Health behavior education Mini-grants awarded to student groups, groups conducted needs-assessments, held health a fare, and developed summer projects to address community needs Poster presentations, questionnaire • Developed leadership skills • Increased understanding of the social determinants of health • Developed understanding of health disparities that could be addressed by health education interventions, community partnerships, and changes to policy/legislative mandates Meili et al, 2011 21 Selective 2 years M1 and M2 (N = 14) Develop social accountability Service-learning program rotates through urban, rural, and international locations (students learn foreign language), qualitative data analysis conducted on open-ended questionnaires Reflective essay • Increased importance of patient-physician relationships • Developed multicultural understanding of community • Increased understanding of the social determinants of health • Increased sense of social justice • Recognized need to affect unhealthy habits of communities • Mixed...…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies in the early clinical experience literature have looked specifically at exposure to pediatrics. Three studies have identified positive outcomes when students interacted with healthy children ( 6 8 ) and only one study by Satran et al ( 9 ) exposed students to pediatric patients in hospital and ambulatory care settings. This study provided insight into the educational benefits of exposing pre-clinical students to children with chronic diseases and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Greater familiarity with aspects of medical practice may allay anxiety about future contact with health services, and may even influence children's future career choices. To our knowledge, this partnership for medical student assessment is unique, although we are aware of a successful university-school partnership focused on teaching clinical paediatric skills in the school setting (McConnell et al 2010).…”
Section: Discussionmentioning
confidence: 99%